Pemberdayaan Masyarakat Melalui Sistem Pertanian Terpadu di Desa Cibodas Kecamatan Pasirjambu, Kabupaten Bandung - Ratnaningsih Ruhiyat; Dwi Indrawati; Etty Indrawati; Lailatus Siami (Institut Pertanian Bogor, 2020)
Integrated farming System (IFS) is a system that combines agricultural activities, farms, and other sciences related to agriculture in one land, so it is expected to be one of the solutions to increase land productivity, and environmental conservation. In implementing the field of IFS implementation to the community, especially farmers and ranchers require guidance and mentoring, so as to perform the IFS run continuously. Empowering the community through Village partnership Development Program (PPDM) aims to improve community empowerment in corn farming, dairy cattle, and make use of waste in Injeman Sub-village, Cibodas Village, Pasirjambu Subistrict, Bandung District. The methods of implementation include counseling, training, focus group discussion, mentoring, as well as the development of land examples IFS. By implementing IFS, then the environment of cow cage becomes cleaner, increased livestock feed from fermented corn waste (silage), the production of organic fertilizer, the existence of renewable energy from cow dung (biogas), and the emergence of Employment from the organic fertilizer business. But in the implementation of the empowerment activities are experienced several obstacles, such as farmers who are not accustomed to use organic fertilizer and ranches who are not accustomed to use silage as livestock feed. Thus it is necessary to mentoring and suppervision both farmers and ranches on the implementation at the following year.